Interdomain routing through QoS-class planes. - Griffin, David
This article presents an approach to delivering qualitative end-to-end quality of service (QoS) guarantees across the multiprovider Internet. We propose that bilateral agreements between a number of autonomous systems (ASs) result in the establishment of QoS-class planes that potentially extend across the global Internet. The deployment of a QoS-enhanced border gateway protocol (BGP) with different QoS-based route selection policies in each of the planes allows a range of interdomain QoS capabilities to coexist on the same network infrastructure. The article presents simulation results showing the benefits of the approach and discusses aspects of the performance of QoS-enhanced BGP.
Keywords: QoS-based route selection policies; QoS-class planes; QoS-enhanced border gateway protocol; Autonomous systems; Bilateral agreements; Interdomain QoS capabilities; Multiprovider internet; Qualitative end-to-end quality of service guarantees